'Native' and 'non‐native' perception of stress in Singapore English. Issue 3 (6th July 2015) - TAN, YING‐YING
ABSTRACT Many scholars have noted how Singapore English (SgE) exhibits different stress placement patterns as compared to British or American English. Much work has also been done to suggest that such deviations of stress placement patterns from the traditional 'native' norms create problems for intelligibility. This study is concerned with the way stress in SgE is perceived by speakers of different Englishes, comparing specifically two groups of participants: the speakers of SgE; and the speakers of British, American and Australian Englishes (the traditional Inner Circle English speakers). The analyses of a perception test indicate that stress is perceived differently between speakers of different Englishes.